Telaah Etika Penyampaian Informasi Berdasarkan Hadis dalam Menanggulangi Hoaks di Masyarakat - Melisa Nur Azizah; Raihan Raihan; Nuruzzalfa Aini; Elan Herlangga; Andi Rosa (STIKes Ibnu Sina Ajibarang, 2025)
One of them is spreading hoaxes, a major challenge that arises in the current technological era that threatens social, political, and religious structures. The purpose of this article is to thoroughly examine the ethical principles of information delivery based on the hadiths taught by the Prophet Muhammad, as well as their relationship to efforts to combat hoaxes in society. The method used in this study is qualitative using a literature research methodology on true hadiths related to honesty, certainty of information (tabayyun), prohibit spreading false information, and the importance of communication intentions. Hadith, according to the research, the Prophet has strong moral values in changing responsive communication behavior. The ethical values contained in the hadith can help build public awareness to prevent hoaxes and build a healthy information culture in the modern era. This is because the hadith can serve as a normative foundation to build public awareness not to easily believe and spread false information.